Hakikat Manusia sebagai Makhluk Pedagogik: Tinjauan Normatif, Perspektif Tokoh Pendidikan dan Teori Kontemporer - Muhammad Mukhtar.S (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2026)
This article explores human beings as pedagogical beings from Islamic normative teachings, educational thinkers, and contemporary theories. It is based on the view that humans possess an innate capacity to learn from birth, as reflected in the Qur’anic command Iqra’ and the concept of fitrah. Using qualitative library research with descriptive-analytical methods, the study analyzes scholarly sources through content analysis and hermeneutics to build an integrative conceptual synthesis. The findings show that humans have fitrah, rationality, and interactive relations with revelation and nature as interconnected sources of learning. Educational thinkers also stress balance among spiritual, intellectual, and social dimensions. The study concludes that education should be holistic and humanistic to optimize human potential comprehensively